(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND In the last decade an increasing number of asylum-seeking children arrived in Europe and local healthcare systems have been challenged to adapt to their health needs. The aim of this study was to compare the spectrum of disease and management of asylum-seeking and non-asylum-seeking children requiring hospital admission. METHODS This was a retrospective cohort study including health data from recently arrived asylum-seeking and non-asylum-seeking children admitted between January 2016 and December 2017. Data were collected using electronic administrative and medical records. RESULTS Of 11,794 admissions of 9407 patients, 149 (1%) were asylum-seeking and 11,645 (99%) from non-asylum-seeking children. In asylum-seeking children the median age was 4 years (interquartile range [IQR] 0–13) with 61% males and in non-asylum-seeking children 4 years (IQR 0–11) years with 56% males. Respiratory infections accounted for 17–19% of admissions in both groups. Rare infectious diseases were more frequent in asylum-seeking children (15 vs 7%; difference in proportions 0.08, 95% confidence interval [CI] 0.02–0.14; p <0.001,). Injuries were more frequent in non-asylum-seeking children (22 vs 13%; difference in proportions 0.09, 95% CI 0.04–0.014; p <0.01). Admissions for mental health disorders were infrequent but more common in asylum-seeking children (6 vs 3%; difference in proportions 0.03, 95% CI −0.01 – 0.07; p = 0.02) Prescription of analgesics was lower in asylum-seeking than non-asylum-seeking children (3.4 vs 6.5 accounting units per admission). Antibiotic prescription was comparable in both groups. CONCLUSION Asylum-seeking children represent a small number of total admissions. Age distribution and main reason for admission being diseases of the respiratory system were comparable in asylum-seeking and non-asylum-seeking children. Rare infections and mental health disorders are important diseases in asylum-seeking children and require special attention and training of staff working with paediatric asylum seekers.